Penerapan SAK EMKM dan PP No.55/2022 Berbasis Excel Untuk Peningkatan Laporan Keuangan dan Perhitungan PPh Final Pada UMKM Brownmix Factory - Evi Andari; Johandri Iqbal; Ivan Ramadhan (Journal of Applied Accounting And Business, 2026)
This study aims to determine how the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and Government Regulation No. 55 of 2022 implemented through excel can improve the quality of financial reports and final income tax calculations at Brownmix Factory MSMEs. The research method used is descriptive qualitative with the type of applied research. Data collection techniques are carried out through observation, interviews and documentation. The results of the study indicate that Brownmix Factory does not yet have systematic financial reports in accordance with SAK EMKM and has not calculated final income tax because it only focuses on recording incoming and outgoing cash and production operational activities. Brownmix Factory has structured, accurate and standardized financial reports and calculates final income tax according to applicable tax regulations after implementing an excel template integrated with SAK EMKM and PP No. 55 of 2022 in its financial recording process.